POLICY CHALLENGES AND OPPORTUNITIES IN ANGKLUNG CONSERVATION: A PERSPECTIVE OF GENERATION Z AS A CULTURAL HERITAGE - Fadillah Nur Islami; Anissa Aulia Rahmasari; Luthfi Ghani Faza; Ricky Hermayanto; Fitri Rahmafitria (Journal Hotspot, 2025)
Angklung, an intangible cultural heritage from West Java, plays an important role in building the cultural identity of the Indonesian nation. The preservation of traditional arts has been hindered by the challenges of globalization and the lack of interest of the younger generation, especially Generation Z, in traditional arts. The purpose of this study is to evaluate the challenges, opportunities, and effectiveness of angklung conservation policies, with a particular focus on the perspective of Generation Z in Bandung. Using a mix-method, this study involved 100 respondents through quantitative surveys, as well as in-depth interviews with members of the art community, such as Saung Angklung Udjo. Although 90,85% of respondents had a high awareness of angklung conservation, only 81.88% comprehended its supporting policies, such as the Bandung City Regional Regulation, according to the findings. Despite the introduction of the tagline 'AWI BITUNG', its effectiveness is still low (71.8%), which indicates the need for more innovative digital promotion. The use of digital technology by Generation Z has the potential to be a conservation agent, but only 84.2% feel the need to actively participate. Collaboration between the art community, the government, and Generation Z through. Technology-based branding and education strategies is the main opportunity for the preservation of angklung. The sustainability of angklung culture as a symbol of local and national pride is recommended by this study through an innovation-oriented cross-sector approach.